Lembaga Pendidikan Sebagai Suatu Sistem Sosial - Mawardi Mawardi (STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur, 2022)
Through the practice of education, learners are invited to understand how historical or cultural experiences can be transformed within days of life they would have done as well as prepare them for the challenges and demands that exist in it. Thus, the meaning of knowledge and culture are often forced to be combined because of their influence on the knowledge era when transformed. National education aimed at preparing a new, more ideal society, ie people who understand the rights and obligations and actively participate in nation-building process. Educational institutions we seem less successful in bringing their students as agents of social change in the community, as evidenced by the absence of significant changes and a thorough review of the problem of culture and science of our society, and the rampant commercialization of science in educational institutions us, high cost of education as well as the orientation of which is only just preparing learners to meet the exchange of labor market rather than look at it as an object that can be set up to become agents of social change in the community